Inflation target credibility in times of high inflation - Winnie Coleman; Dieter Nautz (Freie Universität Berlin, School of Business & Economics, 2022)
We use a representative online survey to investigate the inflation expectations of German consumers and the credibility of the ECB's inflation target during the recent high inflation period. We find that credibility has trended downwards since summer 2021, reaching an all-time low in April 2022. The high correlation between inflation expectations and the actual rate of inflation strongly indicate that inflation expectations have been de-anchored from the inflation target. With increasing inflation, German consumers are more convinced that - in contrast to the ECB's inflation target - inflation will be well above 2% over the medium term.
urn:nbn:de:kobv:188-refubium-35508-9
Keywords: C83; E31; E52; E58; 330; Credibility of Inflation Targets; Household Inflation Expectations; Expectation Formation